Interfacial host–guest complexation for inverted perovskite solar cells (2024)
Perovskite solar cells have demonstrated exceptional development over the past decade, but their stability remains a challenge toward the application of this technology. Several strategies have been used to address this, and the use of host–guest complexation has recently attracted more interest. However, this approach has primarily been exploited in conventional perovskite solar cells based on n-i-p architectures, while its use in inverted p-i-n devices remains unexplored. Herein, we employ representative crown ether, dibenzo-24-crown-8, for interfacial host–guest complexation in inverted perovskite solar cells based on methylammonium and methylammonium-free formamidinium-cesium halide perovskite compositions. Upon post-treatment of the perovskite films, we observed nanostructures on the surface that were associated with the reduced amount of trap states at the interface with the electron transport layer. As a result, we demonstrate improved efficiencies and operational stabilities following ISOS-D-2I and ISOS-L-2I protocols, demonstrating the viability of this approach to advance device stability.